Bridging the science and mathematics divide: Issues, challenges, and promises - Bell-Hutchinson, Camille (School of Education, UWI, St. Augustine, 2008)
The learning of both science and mathematics represents alienating experiences for many students in the Caribbean. This must be cause for concern, since both these disciplines play pivotal roles in the growth and development of a nation. This paper puts forward the position that teachers should more closely link the two subjects in the classroom in order to bring meaning to both. We argue that since both mathematics and science teaching not only share some common learning goals-the development of a spirit of inquiry, the ability to draw conclusions based on evidence, and the ability to reason and solve problems-but also important concepts such as length, area, volume, mass, and time, that learning can be significantly enhanced through classroom practices that deliberately attempt to connect such knowledge, skills, and principles that have clear relevance to both disciplines. Issues and challenges in attempting to bridge the divide will be discussed with implications for teacher education and the associated challenges
Keywords: Mathematics education; Science education; Teaching techniques; Jamaica; Caribbean